ANALYSIS OF INDONESIAN WRITING ERRORS IN BILLBOARD PUBLICATIONS IN LHOKSEUMAWE CITY - Jamilah; Wahdaniah; Putri, Yetty Tri; Ginting, Sridinanta Br (International Journal of Social Science, Educational, Economics, Agriculture Research and Technology (IJSET), 2025)
This study aims to analyze various Indonesian writing errors found on billboards in Lhokseumawe City, Indonesia, including errors in the use of foreign elements, and evaluate the relevance of research findings to Indonesian language learning materials in higher education. The method used in this research is a descriptive qualitative approach, involving the collection of samples in the form of text from billboards in Lhokseumawe. Sampling was done purposively, while data collection techniques included listening and recording. To ensure data validity, source triangulation techniques were used. Data analysis was conducted using an interactive model through four stages, namely data collection, data reduction, data presentation, and verification. The results showed some important findings. First, the most common linguistic errors in outdoor media include word writing errors, especially in diction selection, preposition *di* writing, and the use of abbreviations. Second, errors were also found in the use of English and Acehnese. Third, the findings of this study are considered relevant to be used as teaching materials or references in Indonesian language courses in higher education, especially in the material of EYD, word writing, abbreviations, and elements of absorption.